2009
DOI: 10.2217/nnm.09.77
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Antimicrobial Silver Nanoparticles by The Endophytic Fungus Aspergillus Clavatus

Abstract: AgNPs can be mycosynthesized extracellularly using A. clavatus as the fungal system, which is highly advantageous over chemical synthesis not only because it can be synthesized on a large scale, but because of the ease of downstream processing and its biomedical application in antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(156 citation statements)
references
References 33 publications
9
144
0
3
Order By: Relevance
“…These nanosize particles have also established in vivo encouraging effect as therapeutic agents [3,4]. The studies conducted in past few year, Metal-NPs have been improved for their antimicrobial activity and may locally destroy pathogenic organisms, without being toxic to the surrounding tissue [5][6][7][8]. Previously, there have been numerous reports on the green synthesis of metal nanoparticles [9][10][11] and AgNPs have their own importance among all.…”
Section: Introductionmentioning
confidence: 99%
“…These nanosize particles have also established in vivo encouraging effect as therapeutic agents [3,4]. The studies conducted in past few year, Metal-NPs have been improved for their antimicrobial activity and may locally destroy pathogenic organisms, without being toxic to the surrounding tissue [5][6][7][8]. Previously, there have been numerous reports on the green synthesis of metal nanoparticles [9][10][11] and AgNPs have their own importance among all.…”
Section: Introductionmentioning
confidence: 99%
“…Nirjanta Devi et al, [17] also revealed SPR band for AgNps in the range of 390-440nm by endophytic fungus, Penicillium sp isolated from Centella asiatica plant. Verma et al, [21] also reported SPR peak at 415 nm by endophytic fungus Aspergillus clavatus isolated from the surface sterilized stem tissues of Azadirchta indica. While Sophiya Devi et al, [22] revealed SPR sharp peak at 415nm and 403nm by endophytic fungi Alternaria solani and Penicillium funiculosum respectively isolated from the ethno medicinal plant Gloriosa superb L. All these reports suggest that the peaks shown by almost all the endophytic fungi as per the literature lie in the range of 390-440 nm.…”
Section: 1 Uv-visible Spectroscopymentioning
confidence: 97%
“…Afreen et al, [5] also reported synthesis of AgNps by Rhizopus stolonifer and also reported the increase in colour intensity of AgNps was due to increased number of nanoparticles formed in the reaction mixture. Verma et al, [21] reported biosynthesis of AgNps by Aspergillus clavatus an endophytic fungus isolated from sterilized stem tissues of Azadirachta indica. Sophiya Devi et al, [22] also used endophytic fungi Alternaria solani GS1 and Penicillium funiculosum GS2 isolated from the ethno medicinal plant Gloriosa superb L for extracellular biosynthesis of AgNps.…”
Section: Extracellular Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Fungal mediated synthesis of SNPs has been done by a number of researchers so far. Fusarium oxysporum [7], Aspergillus fumigates [9], Fusarium semitectum [10], Aspergillus niger [11], Cladosporium cladosporioides [12], Penicillium brevicompactum [13], and Aspergillus clavatus [14] have been previously described. An extensive intracellular and extracellular study has been conducted on the biosynthesis of SNPs by Aspergillus species.…”
Section: Introductionmentioning
confidence: 99%